A dialética consciente-inconsciente no desenvolvimento da identidade sexual: aportes sócio-históricos à práxis clínica psicoterápica - Montreozol, Jeferson Renato (2019)
The present work aims to understand the dialectical relations between conscious and unconscious functions and sexuality, which permeate the development of the higher psychological processes of the subjects, among them, the sexual identity. For this, consciousness was approached as a set of functions and processes that enable the subject to know and act on reality and, for this reason, the conception of the unconscious that was assumed takes eminently from the cultural aspects, as dialectical pole of the same relation to consciousness. From these presuppositions, it is understood that the unconscious relates to consciousness and sexuality through non-verbal (sentimental-emotional) configurations and processes, allowing the subject to develop their sexual identifications even without understanding them, that is, making it impossible to develop abstractions to understand how the external reality is affecting it. In support of this thesis, the hypotheses are presented that the sexual identity represents the dialectical synthesis between the consciousness and the unconscious; the reference to the continued development of sexual identity, and not the fixity of such structure; the exclusive appropriation of male and female attitudes and behaviors; the revalidation of the sphere of desire as a possibility for directing the emotional aspects or, still, the emotional tonus; and the markings imposed by capitalist society on the development of sexual identities. Starting from the qualitative assumptions, we opted for the exploratory study and the principles of the bibliographic research were used from the indexes Biblioteca Virtual de Saúde (BVS), Biblioteca Virtual de Saúde - Psicologia (BVS-Psi), SciELO, LILACS, MEDLINE, searching to analyze books, periodicals, theses, dissertations, collections of texts, in physical and online material, in the Portuguese, English and Spanish languages, focusing on the correlation of the conscious-unconscious dialectics, sexuality and sexual identity, socio- historical psychology, cultural-historical psychology and historical-dialectical materialist method. We defined the technique to investigate possible solutions by reading as the main reference to identify the information and data contained in the selected material, as well as to verify the relations between them for an interrelationship and consistency. Thus, the synthetic material presented here aims to expose the possible solutions formed for the research process, beginning with the presentation of studies and theorizations about human sexuality, pointing, from these, a historical-dialectical materialist understanding for the triadic relationship established between sex, gender and sexuality. In the sequence, from the cultural and emotional mediation, the production and the development of the conscious and unconscious instances of the human psyche were discussed. In a third moment, the considerations about the development of processes of identification of the subject with the reality and with himself, mainly with respect to the aspects of the sexuality, based on the conscious-unconscious dialectic were brought. In continuity, the historicity of clinical practice and the possible implications of the historical-dialectical materialist method to psychotherapy were explained, in the production of a therapeutic praxis that makes the historicized clinic as a space for the development of subjective consciousness. After the presented elements, the presented hypotheses are considered true and allow to confirm the thesis defended. Finally, it was pointed out that the psychotherapeutic praxis can enable the movement from the unconsciousness of reality to the sexual identity consciousness, a political position that goes beyond immediate, naive knowledge, ascending to the reflective plane and thus enhancing thought and action